The Urgency of Civic Education in the Nation Character Building - Munasib, Munasib; Muhammad Taufiq; Rifki Ahda Sumantri (COMPETITIVE: Journal of Education, 2023)
Civic Education has an important role in shaping the character of the Indonesian nation. However, in this era, the character has experienced fading due to the times and globalization. Therefore civics education is present as a subject that aims to build the character of the Indonesian nation from the elementary level to tertiary institutions.  This study used a systematic review design. Meanwhile, the systematic review method is based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Met-Analyses) method. The results of this study are that Civic Education has an urgency and role in the formation of Indonesian character and national character originating from Pancasila, in the form of religious attitudes, independence, cooperation, integrity, responsibility, democracy, tolerance, values of freedom, equality, patriotism, nationalism, love of the motherland, and the spirit of defending the country.